Carthage conspiracy : the trial of the accused assassins of Joseph Smith - Oaks, Dallin H. (University of Illinois Press, 1975)
Illuminates Mormon/non-Mormon conflict through dramatic story of Mormon prophet Joseph Smith, his brother Hyrum, and their alleged assassins.